A merry little murder plot - McKinlay, Jenn (McKinlay, Jenn. Library lover's mysteries, 2024)
"During the most wonderful time of the year, famous author Helen Monroe arrives in Briar Creek to be the writer in residence, but her "bah humbug" attitude excludes her from the many holiday celebrations the town residents enjoy. To try to spread some Christmas cheer, library director Lindsey Norris invites the new writer in town to join her crafternoon club. Helen politely refuses, and when an altercation happens between Helen and another patron, Lindsey begins to suspect the author has been keeping to herself for a reason. Another newcomer, Jackie Lewis, reveals she's visiting Briar Creek to be near Helen because she believes they are destined to meet. Having dealt with a stalker in the past, Lindsey feels compelled to tell Helen about Jackie, as she suspects that Helen is unaware her "number one" fan is in town. When Jackie's body is later discovered in the town's park beneath the holiday-light display with a copy of Helen's latest manuscript in her hand, the reclusive novelist becomes the prime suspect in the murder of her self-proclaimed mega fan. Helen's frosty demeanor melts when Lindsey offers her help, and now the librarian and her crafternoon pals must prove the author innocent before "The End" becomes Helen's final sentence"--